The degree of awareness of female students exposed to electronic blackmail in the basic stage of the concepts of moral intelligence and its relationship to the level of blackmail - Alsmeheen, Reema Awwad; Aldalaien, Anas Saleh (Journal of Educational and Psychological Sciences, 2024)
The current study aimed to identify the level of both moral intelligence and the effects of electronic blackmail and their relationship together. To achieve the objectives of the study; a descriptive method was adopted, and two scales for moral intelligence and effects of electronic blackmail were developed, and their psychometric properties were verified for validity and reliability. A sample of female students exposed to electronic blackmail was selected by returning to the girl counselors in the southern governorates. The female counselors responded to the items of the two scales for a sample of (80) female students from the basic stage (Eighth, ninth and tenth), the results indicated1. Female students exposed to cyberbullying exhibit a moderate level of moral intelligence.2. Female students exposed to cyberbullying show a moderate level of its effects.3. There is a statistically significant relationship at a significance level of (α≤0.05) between the effects of cyberbullying and the level of moral intelligence.The study recommended a set of recommendations, the most prominent of which were: conducting further studies on the problem of electronic blackmail and following up on women exposed to blackmail. Of all kinds, and the necessity of planning and following up on indicative treatment programs.
Keywords: Moral Intelligence; Electronic blackmail